Key Drivers of Employee Engagement and Strategic Priorities for Talent Development in an Education Service Company : Case Study: PT Kreasi Edulab - Shafina Abdul Aziz Baraba; Aurik Gustomo (International Journal of Economics and Management Research, 2024)
Employee engagement is a critical factor influencing workforce performance and retention, particularly in education service companies dominated by Generation Z employees. Based on the company's historical turnover data, the company recorded a high turnover rate of 23% in 2022. Although this decreased significantly to 11% in 2024, it rose again to 19% in 2025, indicating persistent challenges in employee retention and signaling the need for more structured talent development strategies. This study aims to identify the key drivers of employee engagement and determine strategic priorities using Multiple Linear Regression (MLR) and Importance Performance Analysis (IPA) to identify the main focus variable. Using data from 260 employees, five engagement drivers were tested: Job Satisfaction & Meaningfulness (JSM), Leadership & Managerial Support (LMS), Team & Work Environment (TWE), Reward–Recognition & Work-Life Balance (RRWB), and Growth, Development & Enablement (GDE). MLR results reveal that GDE is the strongest predictor of employee engagement, emphasizing the importance of structured capability development for a predominantly Gen Z workforce. IPA further shows that GDE falls into Quadrant I (High Importance – Low Performance), indicating a critical performance gap requiring immediate intervention. To address this, the study proposes a Talent Development Program based on the 70:20:10 learning model, combining formal training, social learning, and on-the-job development. This framework offers a data-driven approach to enhancing employee capability, improving engagement, and mitigating turnover fluctuations, supporting Edulab’s long-term organizational sustainability.